Implementasi Audit Planning Berdasarkan Standar Profesional Akuntan Publik Pada Kantor Akuntan Publik Abdul Ghonie Dan Rekan - Diah Aryati Prihartini; Tommy Kuncara; Early Armein (Owner : Riset dan Jurnal Akuntansi, 2023)
Auditing is an examination conducted by an independent party on the financial statements. Prior to the implementation of the audit process, the auditor must prepare an audit plan according to the SPAP audit standard. Audit planning is a stage of the audit process that aims to ensure success in a quality, economical, efficient and effective manner. The purpose of this study was to determine the audit planning applied to KAP Abdul Ghonie and Partners on the audit planning in SPAP. The author's data obtained in the form of Financial Statements used in the Audit Planning at KAP Abdul Ghonie and Partners, such as: Audit risk assessment, understanding of the entity's business and the law, determination of audit scope, preparation of audit plan. After the data was collected, a comparative analysis of the audit planning of Abdul Ghonie and Partners was carried out on SPAP. The results obtained are that KAP Abdul Ghonie and Partners in audit planning are in accordance with SPAP, but KAP Abdul Ghonie and Partners do not comply with international standard audit planning standards that have been approved by IAPI and PP2PK, so it is hoped that KAP Abdul Ghonie and Partners can use the audit application planning in accordance with IAPI to uniform the audit planning model for public accounting firms in Indonesia.